Ion Pair Formation and Thermodynamics of Glycine Bis-1-Amidino-O-Methylurea Cobalt(III) Halides in Water + Methanol Mixed Solvents at Different Temperatures - MOHONDAS SINGH, N.; DAVID SINGH, TH.; YAIPHABA, N.; RAJMUHON SINGH, N. (Asian Journal of Chemistry, 2010)
Conductometric studies have been made for the solutions of glycine bis-1-amidino-O-methylurea cobalt(III) chloride, glycine bis-1-amidino-O-methylurea cobalt(III) bromide and glycine bis-1-amidino-O-methylurea cobalt(III) iodide in water and water + methanol mixtures at different temperatures ranging from 5-35 ºC. The conductance data in all cases have been analyzed by Shedlovsky method to obtain limiting molar conductances (Λo) data and ion association constants (KA) values. The influence of the mixed solvent composition on the solvation of ions has been discussed based on the composition dependence of the Walden product (Λoηo). The thermodynamics parameters viz., changes in enthalpy, entropy and free energy for the ion pair formation have been calculated from the value of ion association constant at different temperatures. The results have been discussed in terms of ion-ion, ion-solvent and solvent-solvent interactions.